Effects of Different Technological Forms of the Perilla frutescens in the Diet on Ruminal Fermentation, Milk and Plasma Fatty Acid Composition, Ruminal Biohydrogenation and Milk Quality in Dairy Goats - Selma Büyükkılıç Beyzi; İsmail Ülger; Emrah Kaya; Buğra Ocak; Yusuf Konca (Veterinary Medicine and Science)
ABSTRACT Background Fatty acids can be protected by changing their structure or form against microbial activity, and the different forms of fatty acids can modulate the ruminal biohydrogenation rate and contribute to the desired fatty acid profile in milk fat. Objectives The study investigated the effects of perilla (Perilla frutescens) dietary supplementation in the diet in different technological forms (seed, oil and formaldehyde‐treated oil) on milk, plasma and ruminal fatty acid composition, and milk quality in lactating goats. Methods The four dietary treatments consisted of (1) no supplementation, basal diet (CON); (2) perilla supplementation as seed at 44.7 g/kg (consisting of 20 g/kg oil (PS)); (3) perilla supplementation as oil at 20 g/kg (PO); (4) perilla supplementation as formaldehyde treated oil at 20 g/kg (protected perilla oil [PPO]). The experiment was implemented in a double 4 × 4 Latin square trial design, and sampling was carried out for 7 days after 21 days of adaptation. Results Performance parameters were not affected by P. frutescens supplementation to the diet. PO decreased milk fat, whereas PPO increased milk fat. Milk cholesterol was not affected by P. frutescens dietary supplementation. Perilla oil supplementation in different forms to the diet did not affect ruminal pH, VFA and methane production. Perilla oil supplementation in different forms to the diet did not also affect the concentration of blood serum glucose, cholesterol and non‐esterified fatty acids. Perilla supplementation to the diet increased the milk conjugated linoleic acid (CLA), C18:3n‐3, C22:5n‐3, C20:5n‐3, C22:6n‐3 and polyunsaturated fatty acid (PUFA) concentrations, and PPO group showed the greatest values. Ruminal palmitic (C16:0) acid was decreased, and in perilla groups, stearic acid (C18:0) concentration had the lowest, and ruminal c‐9, t‐11 CLA concentration had the highest value in PPO. Conclusions It has been found that the most effective form of perilla oil in increasing milk quality is that with formaldehyde treatment (protected form). Perilla oil, which is a rich source of omega 3 in the diet, can be used to increase milk quality in goats without adversely affecting performance, ruminal fermentation and blood parameters.